EFEKTIFITAS LARUTAN UBI JALAR UNGU (IPOMEA BATATAS) DENGAN BUAH NAGA BERDAGING MERAH (HYLOCEREUS POLYRHIZUS) SEBAGAI BAHAN IDENTIFIKASI PLAK (DISCLOSING SOLUTION) - Endah Aryati Ekoningtyas; Sekar Arum Sari; Erni Mardiati; Sulur Joyo Sukendro (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2015)
TITLEEffectiveness of purple sweet potatoes (Ipomea batatas) and red dragon fruit (Hylocereus polyrhizus) as plaque identification agent (disclosing solution)ABSTRACTThe content of the dye in purple sweet potato anthocyanins and carotenoids content of dyes in the red dragon fruit, has the potential a source of natural dyes. Plaque is usually formed on a third surface of the gingival and the tooth surface is rough, form biofilm, known as plaque. Plaque can absorb dyes that can indicate the presence of biofilm. The research objective was to determine differences in the ability of the solution to the purple sweet potato red fleshed dragon fruit as materials identification plaque (disclosing solution).The method used is Experimental Research. Design used is Posttest Only Design. Samples were taken 30 people and divided into 2 groups. Group 1st amounted to 15 people given treatment solution dripping purple sweet potato, and the second group totaled 15 people given treatment solution dripping red dragon fruit. Analysis of the data used in this study is Test Independent Test.The results showed the averages value of the plaque index in a solution of purple sweet potato 2.221 and the average value of the plaque index in the red dragon fruit 2.875. Result of Independent T-test has Sig 0.13 means that there are differences in the ability to use the solution with a purple sweet potato red fleshed dragon fruit as materials identification plaque (p 0.05). As a material it is necessary to identify plaque dyes that can be embedded in dental plaque, antosianin amount of content that has the in herentability of the dye solution and based on research results more red dragon fruit can identify plaque compared with a solution of purple sweet potato. Keywords: Sweet potato purple, red dragon fruit, Plaque Index